Taxonomic Notes on Genus Smilax L. (Smilacaceae) from the Mainland Southeast Asia - Kladwong, Pornchai; Chantaranothai, Pranom (Tropical Natural History, 2020)
Four species of Smilax (S. cambodiana, S. longiflora, S. paniculata and S. setosa) are newly recorded for Thailand and one species (S. leucophylla) is newly recorded for Cambodia. Smilax barbata and S. leucophylla var. platyphylla are lectotypified. Smilax barbata is a superfluous name of S. setosa and S. leucophylla var. platyphylla proposed as a new synonym of S. leucophylla. Detailed descriptions, photographs, illustrations, notes and distribution maps for each of the species are provided.